2008
DOI: 10.4161/auto.6556
|View full text |Cite
|
Sign up to set email alerts
|

A lifespan-extending form of autophagy employs the vacuole-vacuole fusion machinery

Abstract: While autophagy is believed to be beneficial for life-span extension, it is controversial which forms or aspects of autophagy are responsible for this effect. We addressed this topic by analyzing the life span of yeast autophagy mutants under caloric restriction, a longevity manipulation. Surprisingly, we discovered that the majority of proteins involved in macroautophagy and several forms of microautophagy were dispensable for life-span extension. The only autophagy protein that is critical for life-span exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 79 publications
6
64
0
Order By: Relevance
“…It is interesting to note that Atg15 extends yeast life span by mediating intravacuolar membrane disintegration. 35 The role of MrAtg15 in M. robertsii remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that Atg15 extends yeast life span by mediating intravacuolar membrane disintegration. 35 The role of MrAtg15 in M. robertsii remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been reported that autophagy is both independent and dependent on S6K, which is a critical downstream substrate and effector of the TOR pathway. In Drosophila, Scott et al demonstrated that TOR-mediated suppression of autophagy occurs independently of S6K (56). Conversely, it was found that phosphorylation of ribosomal protein S6 inhibits autophagy in rat hepatocytes (45).…”
Section: Lifespan Regulation Independent Of Autophagymentioning
confidence: 99%
“…Micro-organisms: Recently, Tang et al (56) demonstrated that vacuole-vacuole fusion was required for extension of the lifespan of yeast in response to caloric restriction. Furthermore, it has been shown that the autophagy protein, Atg15p, is a lipase located in the ER that is essential for lifespan extension.…”
Section: Lifespan Regulation Dependent On Autophagymentioning
confidence: 99%
“…13 Moreover, while Atg11 operated in processes that protected cells during zinc treatment and leucine starvation, it appeared to interfere or compete with life-extending processes during nitrogen starvation. More subtly, the loss of Atg15, a vacuolar lipase that extends the life span of cells during caloric restriction, 36 switched the primary pathway of death during nitrogen starvation from necrosis to apoptosis. It is possible that cells that are unable to breakdown their autophagosomes in the vacuole, and thus unable to recycle the autophagosome contents, are dying like cells starved for leucine.…”
Section: +mentioning
confidence: 99%